Efek hipoglikemik dan hipolipidemik dendeng daging itik curing dengan ekstrak kurkumin kunyit pada Tikus Wistar - Sri Hartati Candra Dewi; Chatarina Wariyah; Niken Astuti (Universitas Sebelas Maret, 2021)
Objective: This research aimed to determine hypoglycemic and hypolipidemic effects of cured duck meat jerky with curcumin using male Wistar rats as experimental animals.Methods: This research involved a completely randomized design in oneway pattern with 4 treatments on diabetic (TD) and hyperlipidemic (HD) rats : zero jerky (standard feed, PS), low jerky 0.96 g/head/day (DR), high jerky 1.91g/head/day (DT) and vitamin E 28.80 mg/head/day as control antioxidants (equivalent to 400 IU tocopherol). There were 24 rats divided into 4 treatments for hypoglycemic and hypolipidemia each. The treatment spanned 4 weeks, with hypoglycemic parameters (body weight and blood glucose) observed every week, and hypolipidemic (total cholesterol, triglycerides, HDL, and LDL). Furthermore, an analysis of variance was conducted to determine body weight. When a significant difference was observed, it was continued with Duncan's New Multiples Range Test, while other parameters were analyzed descriptively.Results: The hypoglycemic effect showed a significant difference in body weight where the PS treatment were relatively stable, while DT and vitamin E treatment experienced the highest weight loss. Blood glucose also decreased with the increasing addition of curcumin and vitamin E. Meanwhile, the hyperlipidemic showed a decrease in cholesterol, triglycerides, and LDL, while HDL increased as the concentration of curcumin from jerky increased, the amount of which was equivalent to antioxidant control of vitamin E.Conclusions: The diet of cured duck meat jerky as much as 1.91g/head/day (equivalent to 106.26 g/person/day or 400 IU tocopherol/vitamin E) can lower diabetic blood glucose and improve blood lipid profile.